WOMEN'S PERSPECTIVE ON ISLAMIC EDUCATION - Mahadewi Puteri Intan (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2023)
Islam regards men and women as equals with equal rights. However, there are major differences between men and women. This research will look into gender concerns in Islamic education. The study's goal is to assess Islamic education from a gender perspective and learn more about how Islam is taught. This type of inquiry is known as library research. To assess all of the study's data, the researchers used descriptive analytic approaches. Before investigating gender perspectives, the researchers gathered information on Islamic education. The results of this study show that men and women have similar perspectives on the role of women in Islamic education. When a society is peaceful, the issue of gender discrimination can be handled. The study discovered no differences in men's and women's intelligence or ability for thought, and as a result, women had an equal place in Islamic education to men in terms of gender representation.